2021
DOI: 10.1002/aur.2549
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal symptoms and sensory abnormalities associated with behavioral problems in children with neurodevelopmental disorders

Abstract: Behavioral problems directly affect the quality of life of caregivers and children with autism spectrum disorder (ASD) and/or attention‐deficit/hyperactivity disorder (ADHD), and is known to be associated with clinical factors such as gastrointestinal (GI) symptoms, sensory abnormalities, intellectual abilities, and use of medication. However, previous studies have not considered these relationships comprehensively. We conducted a cross‐sectional study of 6–12‐year‐old children with diagnoses of ASD and/or ADH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Data analysis showed that both the control mice and the USP7 mice spent more time interacting with the novel object, and no difference was detected in the discrimination index between the two groups ( Figure 10 N) (Ctrl (n = 8) vs. USP7 (n = 13), p > 0.05, t -test), indicating intact recognition capabilities in mice with USP7 overexpression. In addition, in ASD patients and model animals, alterations were often found in the peripheral somatosensory functions ( Sukoff Rizzo and Crawley, 2017 ; Kurokawa et al., 2021 ). We performed the hot plate assay to evaluate thermal sensitivity in virus-injected mice by measuring the latency of hindpaw withdrawal ( Figure 10 O).…”
Section: Resultsmentioning
confidence: 99%
“…Data analysis showed that both the control mice and the USP7 mice spent more time interacting with the novel object, and no difference was detected in the discrimination index between the two groups ( Figure 10 N) (Ctrl (n = 8) vs. USP7 (n = 13), p > 0.05, t -test), indicating intact recognition capabilities in mice with USP7 overexpression. In addition, in ASD patients and model animals, alterations were often found in the peripheral somatosensory functions ( Sukoff Rizzo and Crawley, 2017 ; Kurokawa et al., 2021 ). We performed the hot plate assay to evaluate thermal sensitivity in virus-injected mice by measuring the latency of hindpaw withdrawal ( Figure 10 O).…”
Section: Resultsmentioning
confidence: 99%
“…The quality of life of caregivers of autistic persons is dependent on behavioral problems in persons with autism. A study by Kurokawa et al, ( 2021 ), indicated a relationship between gastrointestinal symptoms and behavioral problems. Thus, the appropriate assessment and treatment of gastrointestinal symptoms might lead to decreased problematic behavior and improved quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…There was a high rate of medical problems reported for the patients reviewed, including conditions known to provoke behavioural manifestations of distress in people with IDD (Charlot et al ., 2011; Hunter et al ., 2008). Gastrointestinal (GI) problems are common and appear to be associated with behavioural challenges in individuals with IDD (Buie et al ., 2010; Chaidez et al ., 2014; Kurokawa et al ., 2021). For example, constipation and GERD were reported at high rates in the current study (70 and 52% respectively).…”
Section: Discussionmentioning
confidence: 99%